2017
DOI: 10.1177/1368430217695443
|View full text |Cite
|
Sign up to set email alerts
|

A lasting sting: Examining the short-term and long-term effects of real-life group rejection

Abstract: The short-term effects of rejection on state selfesteem, negative affect, and hurt feelings have been examined in many laboratory experiments. These studies generally find that rejection causes an immediate decrease in feelings of personal adequacy and self-esteem AbstractAlthough many studies have examined the short-term effects of rejection in laboratory settings, few have investigated the impact of rejection over time or in real-world contexts. The university sorority recruitment process offers a unique opp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…This work set at three months the minimum duration for an exclusion experience to be considered chronic. Similarly, Martin and colleagues (2017) investigated the long‐term effects of rejection from sorority recruitment on young women. The authors found that women who were rejected from the sorority had lower psychological well‐being three months after the rejection (Martin, Smart Richman, & Leary, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This work set at three months the minimum duration for an exclusion experience to be considered chronic. Similarly, Martin and colleagues (2017) investigated the long‐term effects of rejection from sorority recruitment on young women. The authors found that women who were rejected from the sorority had lower psychological well‐being three months after the rejection (Martin, Smart Richman, & Leary, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…First, the present study provided the first longitudinal empirical causal evidence that chronic exclusion leads to resignation. Indeed, previous studies have only spoken about the long-lasting sting of acute rejection episodes (Martin et al, 2018). Although, as recommended by Selig and Little (2012), arguments favouring causal relationships based on cross-lagged panel analyses should be drawn with care, the present findings are strengthened and supported by their conjunction with (1) converging and independent theoretical predictions from the main psychosocial models on interpersonal devaluationpointing at psychological and behavioural withdrawal as the direct outcome of chronic exclusion (Richman & Leary, 2009;Williams, 2009) -(2) qualitative (Zadro, 2004), crosssectional (Marinucci & Riva, 2020), and quasi-experimental (Riva et al, 2017) preliminary evidence of the exclusion-resignation link, and (3) converging results coming from conceptually related scientific fields.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, researchers need to apply methodologies pointing at causal inference (e.g., longitudinal study) that can distinguish between the effect that perceived chronic exclusion can have on the long-term resignation outcomes from the reciprocal influence that resignation can play in generating long-term feelings of being rejected and ostracized. This is the case, for example, of the longitudinal study by Martin et al (2018) investigating the short-and long-term effects of rejection from university sorority recruitment. The authors showed that the negative implications for participants' well-being caused by an acute episode of rejection could last for three months.…”
Section: Subjective Versus Objective Chronic Social Exclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social relationships help us meet evolved needs for acceptance and belonging ( Baumeister and Leary, 1995 ) and they provide us with numerous benefits, such as social support, and access to resources ( Leary and Acosta, 2018 ). As such, events that threaten social relationships or suggest possible social devaluation are experienced as aversive and have harmful effects on one’s cognitions, emotions, behaviors, and physiology ( Leary et al, 1995 ; Stroud et al, 2000 ; Dickerson and Kemeny, 2004 ; Zadro et al, 2004 ; Blackhart et al, 2007 ; Martin et al, 2018 ). SET is one such event.…”
Section: Introductionmentioning
confidence: 99%